Novel benzodithiophene type low band gap polymer solar cell application and device stability study with atomic layer deposition encapsulation technique. (20th September 2019) - Türkmen, Tülin Ateş; Öztürk, Soner; Ç𝚤rpan, Ali; Yerli, Yusuf; Aslan, Emre; Mucur, Selin P𝚤ravad𝚤l𝚤; Parlak, Elif Altürk
Abstract: Novel benzodithiophene type copolymer was synthesized through a solvent evaporation technique. Poly(5-(5-(4, 8-bis((2-ethylhexyl)oxy)benzo[1, 2-b:4, 5-b']dithiophen-2-yl)thiophen-2-yl)-2, 3-bis(3, 4-bis(decyloxy)phenyl)-8-(thiophen-2-yl) quinoxaline) (P-TQTBDT) solar cells were encapsulated with conventional and Atomic Layer Deposition (ALD) techniques. Characterizations of the samples were carried out via nuclear magnetic resonance (NMR), gel permeation chromotagraphy (GPC) and cyclic voltammetry (CV) techniques. Stability studies were carried out both P3HT and P-TQTBDT solar cells for comparison of commercial P3HT and our novel polymer solar cell. Our results confirm that ALD is a promising technique for encapsulation of polymer solar cell since stability of P-TQTBDT improved to 72% durability from 38% durability with ALD encapsulation technique during 300 h under AM1.5 G solar irradiation. P-TQTBDT solar cell showed higher stability (about 10%) than P3HT solar cell for both encapsulation methods. We focused on the stability of polymer solar cell can be improved with ALD encapsulation technique. Our aim was to compare P-TQTBDT polymer solar cell with P3HT solar cell. The stability results of P-TQTBDT showed that P-TQTBDT copolymer could be promising polymer to obtain very high stability of polymer solar cells.